Comparison of meat quality attributes of improved native chicken varieties Vanaraja and Indbro with Commercial broiler chicken - S, Sneha Priya; M, Shashi Kumar; M , Muthu Kumar; A, Vijaya Kumar (Journal of Meat Science, 2023)
There is great demand for native chicken meat due to its unique strong flavour, firm and hard texture and lower fat content and fetches almost thrice the price of broiler meat. During the last few years, improved native chicken varieties are being introduced to meet the demand and the market share is steadily increasing. The present study was conducted to compare the carcass characteristics and meat quality attributes of improved native chicken varieties viz., Vanaraja (dual purpose chicken) and Indbro (slow growing coloured broiler) with Commercial broilers. In this study, total of 30 birds, comprising 10 birds each from Vanaraja (56 days old), Indbro (49 days old), and Commercial broilers (38 days old) at their respective marketable age were selected for evaluation. Analysis of carcass traits revealed significantly (P<0.05) higher live wt, dressed carcass wt, and breast yield (% of live wt) for Commercial broilers compared to Indbro and Vanaraja birds, whereas the yield of legs, wings, and neck (% of live wt) were higher for Vanaraja birds compared to other groups of birds. The results of meat quality parameters like proximate composition revealed significantly (P<0.05) higher % of moisture, protein, and ash for meat of Vanaraja birds compared to other groups, whereas fat % was significantly (P<0.05) higher in Commercial broilers. Significantly (P<0.05) higher redness (a*) values, lower lightness (L*) values, higher muscle fibre diameter and hydroxyproline content was noticed in Vanaraja birds compared to other groups. Commercial broiler chicken meat showed significantly (P<0.05) higher pH, TBARS and water holding capacity (%) values compared to other groups. Sensory evaluation scores for cooked breast meat samples revealed comparatively higher appearance, flavour, juiciness, texture, and overall acceptability scores for Vanaraja and Indbro birds than Commercial broilers. Shear force values were significantly (P<0.05) higher for Vanaraja followed by Indbro and then Commercial broilers. Microbial analysis indicated lower total plate count (TPC), yeast and mould and psychrotrophic counts for Commercial broilers. The results of study indicated that though the Commercial broilers have better carcass traits compared to Vanaraja and Indbro birds, these improved native chicken varieties have better meat quality attributes and have potential to form a significant source of chicken with better sensory attributes.